2003
DOI: 10.1074/jbc.m305542200
|View full text |Cite
|
Sign up to set email alerts
|

Cell Death Caused by Selenium Deficiency and Protective Effect of Antioxidants

Abstract: Selenium is an essential trace element and it is well known that selenium is necessary for cell culture. However, the mechanism underlying the role of selenium in cellular proliferation and survival is still unknown. The present study using Jurkat cells showed that selenium deficiency in a serum-free medium decreased the selenium-dependent enzyme activity (glutathione peroxidases and thioredoxin reductase) within cells and cell viability. To understand the mechanism of this effect of selenium, we examined the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
151
1
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 221 publications
(163 citation statements)
references
References 54 publications
8
151
1
3
Order By: Relevance
“…However, the recombinant form of human transferrin remains to be developed, and purified human or bovine proteins were used in this study. Additionally, selenium is also believed to be an essential trace element for cell culture under serum-free conditions (McKeehan et al, 1976), probably due to its protective antioxidant effects (Saito et al, 2003). However, although the modified KCM was without transferrin or selenium, the efficiency in promoting the successful fabrication of canine oral mucosal epithelial cell sheets was similar to that of the control KCM formulation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the recombinant form of human transferrin remains to be developed, and purified human or bovine proteins were used in this study. Additionally, selenium is also believed to be an essential trace element for cell culture under serum-free conditions (McKeehan et al, 1976), probably due to its protective antioxidant effects (Saito et al, 2003). However, although the modified KCM was without transferrin or selenium, the efficiency in promoting the successful fabrication of canine oral mucosal epithelial cell sheets was similar to that of the control KCM formulation.…”
Section: Discussionmentioning
confidence: 99%
“…Selenium modulates p53 activity by a redox mechanism through the redox factor Ref1 (43), or by a phosphorylation mechanism (44), and inhibits NF-nB and p38 signaling pathways (45,46). On the other hand, it was recently shown that selenium deficiency caused cell death due to accumulation of reactive oxygen species, especially lipid peroxides (47). This effect probably explains the results of Novoselov et al showing antihepatocarcinogenic effect in a transgenic mouse model both at high levels of selenium and at selenium deficiency but not at intermediate selenium levels (12).…”
Section: Discussionmentioning
confidence: 99%
“…Marino et al (2004) showed that vitamin E protects against alcohol induced oxidative stress. The presence of selenium in combination with vitamin E enhanced its activity in removing free radicals and prevented their formation (Saito et al, 2003).…”
Section: Introductionmentioning
confidence: 99%